Single-site multiport vs. conventional multiport robot-assisted radical prostatectomy: A propensity score matching comparative study - Hou, Weibin; Wang, Bingzhi; Zhou, Lei; Li, Lan; Li, Chao; Yuan, Peng; Ouyang, Wei; Yao, Hanyu; Huang, Jin; Yao, Kun; Wang, Long (Frontiers in Surgery, 2022)
Objective Robot-assisted radical prostatectomy (RARP) is a dynamically evolving technique with its new evolution of single-site RARP. Here we sought to describe our extraperitoneal technique, named the single-site multiport RARP (ssmpRARP) using the da Vinci Si® platform and compare it with the transperitoneal conventional multiport RARP (cmpRARP). Materials and Methods Data were retrospectively collected for patients who underwent RARP for localized prostate cancer from June 2020 to January 2022 in a single center. Propensity score matching was performed based on age, prostate size, body mass index, neoadjuvant hormonal therapy usage, prostate-specific antigen levels, and clinical T stage. The differences between the matched two groups were investigated. Results Of the patients, 20 underwent ssmpRARP and 42 underwent cmpRARP during the period. After matching, 18 patients from each group were selected. Median follow-up was 7.8 months (2–12 months) for the ssmpRARP group, and 15.0 months (3–26 months) for cmpRARP. The demographic features between the two groups were comparable. The median total operative time, estimated blood loss, pathologic data, early follow-up outcomes, and hospitalization stays and costs were similar between the two groups. The ssmpRARP group tended to return to their bowel activities earlier (44.78 ± 10.83 h vs. 54.89 ± 12.97 h, p = 0.016). There were no significant differences in complication rates. Conclusions We demonstrated the feasibility and safety of performing extraperitoneal ssmpRARP using the da Vinci Si® robotic platform. Our technique showed comparable short-term outcomes with the transperitoneal cmpRARP. Prospective trials and long-term follow-up are necessary to confirm these results.